Metabolomic and Pharmacologic Insights of Aerial and Underground Parts of Glycyrrhiza uralensis Fisch. ex DC. for Maximum Utilization of Medicinal Resources - Jiang, Liang; Akram, Waheed; Luo, Biaobiao; Hu, Sheng; Faruque, Mohammad Omar; Ahmad, Shakeel; Yasin, Nasim Ahmad; Khan, Waheed Ullah; Ahmad, Aqeel; Shikov, Alexander N.; Chen, Jian; Hu, Xuebo (Frontiers in Pharmacology, 2021)
The roots of Glycyrrhiza spp. have been utilized in traditional Chinese medicine for thousands of years. Non-traditional (aerial) parts constitute a large portion of the biomass of Glycyrrhiza plants and are mostly discarded after harvesting the roots and rhizomes. Through comparative phytochemical and anti-inflammatory activity analyses, this study explored the potential benefits of the aerial parts of G. uralensis as medicinal materials. First, a combined approach based on GC/MS and UPLC-ESI-QTof MS analysis was adopted for the identification and quantitative examination of medicinally important compounds from G. uralensis. Additionally, a bioassay-guided fractioning of ethanolic extracts of G. uralensis leaf material was performed and its anti-inflammatory activity was tested. The aerial portion of G. uralensis was rich in medicinally important compounds. Two compounds (henicosane-1 and decahydroisoquinoline-2) were found to exert a significant anti-inflammatory effect, inhibiting the release of pro-inflammatory mediators (NO and PGE2) and cytokines (IL-1β, IL6, and TNF-α), without exerting cytotoxic effects. Moreover, both compounds down-regulated iNOS and COX-2 mRNA expression. These results sug-gest that non-traditional parts of G. uralensis are suitable sources of bioactive metab-olites that can be explored for medicinal purposes.